2016
DOI: 10.1021/acs.biochem.6b00409
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characterization of Aerobactin Synthetase IucA from a Hypervirulent Pathotype ofKlebsiella pneumoniae

Abstract: Iron is a vital mineral nutrient required by virtually all life forms to prosper; pathogenic bacteria are no exception. Despite the abundance of iron within the human host, highly regulated iron physiology can result in exceedingly low levels of iron bioavailable to prospective invading bacteria. To combat this scarcity of iron, many pathogenic bacteria have acquired specific and efficient iron acquisition systems, which allow them to thrive in iron-deficient host environments. One of the more prominent bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 52 publications
3
51
1
Order By: Relevance
“…Functional characterization of the Type A NIS synthetase AcsD described a highly stereoselective mechanism for the condensation of citrate and L-serine (38). Furthermore, structural models of the AcsD and IucA active sites predicted a mechanism in which only one of the two pro-chiral carboxymethyl groups of citrate is activated by ATP to form a citryladenylate intermediate (36,38). Experiments presented herein confirmed the structural predictions by functionally demonstrating the stereoselective mechanisms of IucA and IucC.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Functional characterization of the Type A NIS synthetase AcsD described a highly stereoselective mechanism for the condensation of citrate and L-serine (38). Furthermore, structural models of the AcsD and IucA active sites predicted a mechanism in which only one of the two pro-chiral carboxymethyl groups of citrate is activated by ATP to form a citryladenylate intermediate (36,38). Experiments presented herein confirmed the structural predictions by functionally demonstrating the stereoselective mechanisms of IucA and IucC.…”
Section: Discussionsupporting
confidence: 69%
“…Finally, we report the steady-state kinetics, and structural characterization of IucC by X-ray crystallography and small-angle solution scattering. Together with our previous studies of IucA (36), hvKP IucA and IucC represent the first pair of Type A and Type C NIS synthetases from a single pathway to be structurally and functionally characterized. This work furthers our understanding of NIS biosynthesis and provides the biochemical and structural foundation to further explore this potential antivirulence target.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…Whole-genome sequencing indicated that KP91 belonged to the ST42 group and contained multiple antimicrobial resistance genes, including the β-lactam resistance genes bla SHV-1 and bla CTX-M-14 , aminoglycoside resistance genes strA , strB , armA , and aph(4)-Ia , macrolide resistance genes mph (E) and msr (E), quinolone resistance genes oqxA and qnrB4 , sulfonamide resistance genes sul1 , sul2 , and sul3 , tetracycline resistance genes tet (A), tet (B), and tet (34), and trimethoprim resistance gene dfrA12 (Table 1 ). KP91 also carried multiple virulence genes, including kfuC , mrkABCDF , irp2 , iucA and iucB , which have been associated with urinary tract infections, septicemia, and pneumonia 19 21 .…”
Section: Resultsmentioning
confidence: 99%
“…Strains of hvKP typically possess biosynthetic and transport genes for aerobactin (iucABCD and iutA) and salmochelin (iroBCDN) on the virulence plasmid [12]. Aerobactin has been shown to be a critical virulence factor under some circumstances [25], leading to aerobactin synthetase (IucA) being thoroughly investigated [26]. Russo et al recently demonstrated that aerobactin is a key marker that distinguishes hvKP from non-hvKP strains [27].…”
Section: Introductionmentioning
confidence: 99%